2007
DOI: 10.1590/s0102-05362007000200035
|View full text |Cite
|
Sign up to set email alerts
|

Produção e qualidade de frutos de tomateiro cultivado em substrato com zeólita

Abstract: O tomate é uma das mais importantes hortaliças no mundo, tanto na área cultivada como no seu valor comercial. O Brasil ocupa o oitavo lugar entre os países produtores, sendo esta hortaliça a segunda em importância econômica no país. Os frutos destinam-se especialmente para o processamento, mas também para o consumo in natura (Filgueira, 2000).O mercado hortícola tem se tornando mais exigente, demandando alternativas viáveis para o aumento quantitativo da produção e a manutenção do fornecimento o ano todo, espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
2
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 20 publications
1
9
2
5
Order By: Relevance
“…Bernardi et al (2007) reported, when producing in a protected environment, that the amount of ascorbic acid varied from 7 to 23 mg ascorbic acid•100 g −1 of pulp; these values are thus lower than the ones observed in this study.…”
Section: Resultscontrasting
confidence: 92%
“…Bernardi et al (2007) reported, when producing in a protected environment, that the amount of ascorbic acid varied from 7 to 23 mg ascorbic acid•100 g −1 of pulp; these values are thus lower than the ones observed in this study.…”
Section: Resultscontrasting
confidence: 92%
“…Since it promotes better firmness, which is one of the most important quality characteristics, both for tomatoes dedicated for fresh and for industrial consumption (Bernardi et al, 2007), this rootstock enables harvesting in advanced stage of fruit ripening, without damaging the quality.…”
Section: Resultsmentioning
confidence: 99%
“…calculated by the formula: T.I. = (soluble solids x % juice) / 100; e) pH determination in digital pH; f) titratable acidity determined according to the AOAC (1995): in 10 ml of juice, titration was performed with 0.5 N NaOH to pH 8.0, and the results were expressed as % (mg citric acid / 100 mL of ); g) ratio: ratio between soluble solids content and titratable acidity and h) ascorbic acid content according to CARvAlHO et al (1990): 10 ml of juice were placed in Erlenmeyer flask containing 50 mL of 1% oxalic acid solution. titration was performed with DCFI (2,6-dichlorophenol indophenol) until persistent pink coloration was achieved for 15 seconds.…”
Section: Plantmentioning
confidence: 99%